1994
DOI: 10.1111/j.1528-1157.1994.tb02554.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Subdural Strip Electrocorticographic Monitoring of Ictal Déjà Vu

Abstract: We report a series of 8 patients with ictal déjà vu. Subdural strip electrocorticographic (ECoG) monitoring localized the ictal epileptogenic focus as follows: right (n = 6) and left (n = 2) mesiotemporal lobe. In all 8 patients, the left hemisphere was dominant for language function based on intracarotid amytal testing. In 6 right-handed patients, ictal déjà vu was associated with a right temporal lobe focus. However, in the 2 left-handed patients, the ictal focus was left temporal lobe. Although ictal déjà v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 22 publications
3
27
0
Order By: Relevance
“…Asterisks represent significant differences (p < 0.05) identified with binomial comparisons temporal neocortex, such propagation of activity occurred only rarely and was confined to its depth -it did not involve the lateral surface. Furthermore, Vignal et al (2007; see also Weinand et al 1994) report that DV does not occur during stimulation of medial temporal lobe structures when afterdischarge was observed in the temporal neocortex, nor during spontaneous epileptic seizures involving both the medial and lateral cortex (i.e. middle and superior temporal gyri).…”
Section: Behavioral Characterizationmentioning
confidence: 92%
See 1 more Smart Citation
“…Asterisks represent significant differences (p < 0.05) identified with binomial comparisons temporal neocortex, such propagation of activity occurred only rarely and was confined to its depth -it did not involve the lateral surface. Furthermore, Vignal et al (2007; see also Weinand et al 1994) report that DV does not occur during stimulation of medial temporal lobe structures when afterdischarge was observed in the temporal neocortex, nor during spontaneous epileptic seizures involving both the medial and lateral cortex (i.e. middle and superior temporal gyri).…”
Section: Behavioral Characterizationmentioning
confidence: 92%
“…Gloor et al (1982) observed that DV was elicited in TLE patients by stimulation of limbic structures (i.e. amygdala, hippocampus, and parahippocampus), sometimes involving afterdischarge in the temporal neocortex (see also Weinand et al 1994;Vignal et al 2007). Similarly, Bartolomei et al (2004) conclude that stimulation of the entorhinal cortex is most likely to induce pathological DV.…”
Section: Introductionmentioning
confidence: 90%
“…In all 8, seizures arose in the hemisphere non-dominant for handedness (that is, the hemisphere ipsilateral to the dominant hand). They concluded that "handedness rather than language dominance appears to be a more consistent predictor of ictal déjà vu lateralisation" and suggest the value of déjà vu as a localising and lateralising characteristic in epilepsy [51]. This contrasts sharply with the failure of Gloor and colleagues to find lateralising features when they examined "experiential phenomena" as a whole -including those in the visual and auditory domains and jamais vu [18].…”
Section: ■ Neuroanatomymentioning
confidence: 93%
“…In a report of a patient with ictal déjà vu and seizures of right hippocampal origin, Gloor concluded that déjà vu, if strictly defined, is sufficient to localise an epileptogenic focus to the right temporal lobe [17]. Questioning the neuroanatomical value of stimulation studies, Weinand and colleagues [51] used subdural strip electrocorticographic monitoring in 8 epileptic patients with preictal déjà vu. 6 were right-handed and 2 left-handed.…”
Section: ■ Neuroanatomymentioning
confidence: 98%
“…The emotion of fear as an aura is highly associated with a right temporal lobe seizure focus (10). The aura of déjà vu in a temporal lobe seizure is also highly correlated with epileptic activity arising from the right hemisphere, usually involving the medial temporal lobe (11), and may be even more accurately associated with temporal lobe seizures arising from the hemisphere nondominant for handedness (12). There are limited reports of experiential auras also being associated with extratemporal pathology (13).…”
Section: Introductionmentioning
confidence: 98%